Англо-русский толковый словарь PC - Григорьев Вячеслав Леонидович (Компьютер, 1997)
Экземпляры: аб. (1998) / Инвентарный номер: 40549 / Цена: / Сис.шифр: 81.2Англ / Авт.знак: Г 83 / ГРНТИ: 16.31.61 / ББК: 81.2Англ-4